A COMPARATIVE STUDY ON DYED AND UNDYED SOYA BLEND MATERIAL USING NATURAL EXTRACT - Jayakumari, M.; Divya, R. (IJRDO-Journal of Applied Science, 2016)
Soya Protein Fiber (SPF) is the only protein fiber made from soybean cake. Their physical properties are similar to that of synthetic fiber. Properties like smoothness/luster/comfort/absorbency/strength/shrinkage shows tremendous range when blended with other fibers. Recent studies shows that when soybean fibers blended with cashmere, it gives smooth quality with an enhancement of easy care properties. As a wool/soy protein fiber, it reduces shrinkage and increases ease of care. As a silk blend, it improves the properties of silk with the prevention of the fabric from sticking to the skin when wet. In this study soya cotton blended fabric is dyed with Indian madder with lime bark as a mordant which is a extract of a plant. A comparative study between dyed and undyed soya cotton blended fabric is tested and evaluated as per Drapablity, Abrasion resistance, Sinking test, Capillary rise and shrinkage.